Fuel Poverty Awareness: A Preliminary Study of New Zealand Tenants - Rasheed E; Holliday L; Mohanty N (Massey University)
Fuel poverty is an issue that has been documented to affect many low-income households in New Zealand. Many studies have shown the effects of fuel poverty to include health and mortality issues during winter periods in the country. To eradicate fuel poverty, sufficient information should be provided to not only decision makers but those directly affected – low-income earners. This study is aimed at investigating the level of awareness of low-income earners to fuel poverty and its effect on their health and comfort. A two-stage survey was carried out on tenants in low-income tenants within Auckland city. This survey involved a questionnaire survey of tenants and physical observation of tenants’ households in Auckland City, New Zealand. The results show that there is insufficient awareness of fuel poverty amongst tenants. Also, the majority (80%) do not seek advice on fuel poverty and the associated effects. The results further showed that there is still evidence of fuel poverty in these households. The implication of this study calls for more efforts to be made by the appropriate authorities to inform the public, in particular, those affected, about fuel poverty. This pilot study was carried out on a small population of low-income earners. More studies are required across the country for the results to be generalised.